2014
DOI: 10.3748/wjg.v20.i40.14950
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of globular adiponectin in diabetic rats with nonalcoholic fatty liver disease

Abstract: AIM:To explore the therapeutic role of globular adiponectin (gAd) in high-fat diet/streptozotocin (STZ)-induced type 2 diabetic rats with nonalcoholic fatty liver disease (NAFLD). METHODS:Seven rats were fed a basic diet (normal control group; NC) during the experiment. Experimental rats (14 rats) were given a high-fat diet for 4 wk and were then injected with STZ to induce type 2 diabetes mellitus (T2DM) and NAFLD. Half of the T2DM/NAFLD rats were randomly injected intraperitoneally with gAd for 7 d (gAd-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Direct pharmacological administration of adiponectin has been shown to reduce glucose, lipid, and insulin concentrations and increase insulin receptor expression in obese diabetic mice on high fat diet [ 105 ]. A study by Kase et al (2007) reported that treatment with globular adiponectin stimulated NF- κ B of activated B cells and increased the expression of cohesive molecules and MCP-1 in endothelial cells by stimulation of the sphingosine kinase signaling pathway [ 106 ].…”
Section: Adipokines As Therapeutic Targets For Vascular Dysfunctiomentioning
confidence: 99%
“…Direct pharmacological administration of adiponectin has been shown to reduce glucose, lipid, and insulin concentrations and increase insulin receptor expression in obese diabetic mice on high fat diet [ 105 ]. A study by Kase et al (2007) reported that treatment with globular adiponectin stimulated NF- κ B of activated B cells and increased the expression of cohesive molecules and MCP-1 in endothelial cells by stimulation of the sphingosine kinase signaling pathway [ 106 ].…”
Section: Adipokines As Therapeutic Targets For Vascular Dysfunctiomentioning
confidence: 99%
“…Moreover, the overexpression of adiponectin in mice is sufficient to improve insulin sensitivity in high fat diet-induced obesity mice models [ 60 , 61 ]. Recombinant adiponectin administration is sufficient to improve glucose, lipid, and insulin plasma levels as well as insulin receptor expression and liver steatosis in high fat diet-induced obesity mice treated with streptozotocin [ 62 ]. This indicates that adiponectin may ameliorate type 1 diabetes and other obesity-related diseases.…”
Section: Adiponectinmentioning
confidence: 99%
“…Rao et al showed that adiponectin can increase insulin secretion in MIN6 cells [ 32 ]. Moreover, globular adiponectin supplementation increased insulin secretion and decreased glucose levels in rats with Type 2 diabetes and NAFLD [ 33 ]. Several medicinal-herb extracts showed hypoglycemic effects that promoted insulin secretion, in accordance with our results [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%